Memantau Tumbuh Kembang Balita Masa Pandemi Covid-19 dengan Aplikasi Primaku di Wilayah Kerja Puskesmas Sitadatada - Sitompul, Emilia Silvana; Simbolon, Juana Linda; Panggabean, Hetty W. A (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
Fetus in the womb until the child is 2 years old is a very important period in the growth and development of children. Good and adequate nutrition, good health status, proper parenting and proper stimulation during this period will help children to grow up healthy and able to achieve their optimal abilities so that they can contribute better. In the community, the Covid-19 pandemic has caused parents to limit themselves from visiting hospitals, Puskesmas, Posyandu, etc. Primaku is an application that makes it easier for parents to monitor children's growth and development on a regular and ongoing basis and this application is recommended by IDAI. Mothers who have toddlers in monitoring the growth of their children's development in home by applying the Primaku Application. The method of implementing the activity is to record data on mothers who have toddlers in the working area of the Sitadatada Health Center from an initial survey of stabilization and determination of locations and facilities and breastfeeding of matent materials. Implementation of service with pre-test training and post-test/evaluation. The results of the majority of ash are already skilled in using the Primaku application to detect the growth and development of Toddlers.